PROPORTION: CLAIM, REBUTTAL AND BACKING DATA BASED ON TEACHER QUESTIONS AS REASONING INDICATOR OF PROBLEM BASED LEARNING IN HIGHSCHOOL SYSTEM REPRODUCTIONS - Widoretno, S.; Dwiastuti, S.; Sajidan, S. (Jurnal Pendidikan IPA Indonesia, 2016)
The reseach purpose is to compare learning proportion of the students based on arguments to learners Claim which is supported by facts, data and theories between conventional learning and PBL as the answers for teacher questions. Research Procedure began with 4 times biology teachers discussion workshops to compile PBL learning plan to be used on treatment class. 61 participants with 30 in control class and 31 in treatment class. Reasoning calculation based on arguments during communication in form of the answers to teacher questions. Basic Grouping of Learning is : Claim Rebuttal (CR), Claim Data (CD), Claim Backing (CB) and Claim (C). Results indicates that: C decreases during PBL learning; CB increases during PBL; CDÂ  doesnât exhibit real change during PBL. PBL utilization needs the readiness and competence of the teachers which influences the reasoning quality of the learners.